MAZARAAT CHEESE CONSUMER PURCHASING DECISION - Lestari*, Indah Ria; Sumarwan**, Ujang; Muflikhati**, Istiqlaliyah (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2020)
This study aims to identify the characteristics of Mazaraat consumers, analyze the influence of customer perceived value (CPV), brand awareness, consumer knowledge, and marketing mix on Mazaraat cheese consumer purchasing decisions, and develop appropriate managerial implications to improve Mazaraat consumer purchasing decisions. The study used 158 local Mazaraat consumers as respondents surveyed using a questionnaire and the data obtained were processed using SEM-PLS. The results showed that customer perceived value, brand awareness, and product variables had a positive and significant influence on purchasing decisions. Meanwhile, the variables of consumer knowledge, promotion, price, and location did not have a significant influence on purchasing decisions. Overall, the product has the most significant direct and indirect influences on purchasing decisions for Mazaraat cheese. The companies should pay attention to the marketing mix variables and other connecting variables to improve the purchasing decisions of Mazaraat cheese.Keywords:Artisan cheese, Brand awareness, Customer perceived value, Consumer knowledge, Marketing mix, Purchase decision* School of Business, IPB University, Jl. Raya Padjajaran, Bogor 16151, Indonesia ** Department of Family and Consumer Science, IPB University. Jl. Kamper, Wing 4 Level 5, Campus of IPB Dramaga Bogor 16680, Indonesia  https://doi.org/10.21632/irjbs.13.1.81-98